DAMPAK PANDEMI VIRUS COVID-19 PADA PENGUSAHA SALON BARBER DI SURABAYA SELATAN - Izzatunnisa, Aisya Aurora; Pritasari, Octaverina Kecvara (Journal of Beauty and Cosmetology (JBC), 2021)
The Covid-19 pamdemic has a major impact on all sectors of life including the business sector. Barbershop is one of the many businesses in the service sector that has been affected by the pandemic. The existence of a physical and social distancing policy causes the community to be anxious when carrying out activities outside, let alone physical contact with other people. This policy caused a decrease in income or turnover for barbershop entrepreneurs due to the decline in the number of customers after the pandemic-related policies were implemented. The purpose of this study was to determine 1) the impact of the Covid-19 pandemic on  barbershop businesses in South Surabaya and 2) the strategies carried out by barbershop businesses in increasing sales turnover. This study used descriptive qualitative method. Data were collected by conducting interviews and direct observation at several salons located in the South Surabaya area. The data obtained is described in such a way so that it can be understood easily. The results of this study were obtained from descriptions of the results of observations made at several salons in South Surabaya. From the observations made, the results obtained were 1) the Covid-19 pandemic had an impact in the form of a decrease in the turnover or income of a number of barber businesses. 2) There are several strategies that can be implemented and have been carried out by barber entrepreneurs, including providing homeservice services, providing services with due observance to health protocols to providing good sanitation. Of these strategies, the strategy stated to be the best is the provision of services by observing health protocols because they are more accessible.Keywords: barber, covid 19 impact